RANCANG BANGUN PENDETEKSI TEMPAT PARKIR KOSONG BERBASIS CITRA DIGITAL - Zunaidi, Achmad Yusuf; Harianto, Harianto; Wibowo, Madha Christian (Journal of Control and Network Systems, 2013)
Parking area and many cars parked in the parking can be an obstacle for those who want to park in the parking  to find out which part is still empty, so it make person must looking around the parking for search an empty spot. At this time the park is equipped with CCTV cameras that are useful only to monitor the parking situation. The resulting image of CCTV can be use actual process to be able to detect an empty parking area and the results will representative as information to the people who want to park. In this final project will be designed a system can detect and inform an empty parking area with background subtraction method using a system consisting of three main parts, namely cameras, computers, and displays. At trial program can produce valid results, but in this program only 3 car caught on camera. So as to develop this system, as the system is designed to take pictures with a concept of panoramic view to getting the image of car that much more.